2019
DOI: 10.1080/17461391.2019.1572227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individualized resistance training prescription with heart rate variability on individual muscle hypertrophy and strength responses

Abstract: The aim of the present study was to investigate if resistance training (RT), performed with individualized recovery between sessions (RT-IND), promotes greater gains in strength and muscle mass and reduces the variability on adaptations compared to RT with fixed recovery intervals (RT-FIX). Twenty young men (age 21.9 ± 3.3 years) were randomized in the RT-IND and RT-FIX groups. Five days before the beginning of the training, measurements of the root mean square of successive R-R intervals differences (RMSSD) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…We observed no significant differences between groups on improvements in maximal squat, OH press, deadlift, and CrossFit total. The lack of observed group differences is similar to the findings of De Oliveira et al [13] on maximal strength in young resistancetrained men undergoing HRV-guided training. However, De Oliveria et al [13] used HRV to augment training frequency, while we used HRV to modulate training intensity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed no significant differences between groups on improvements in maximal squat, OH press, deadlift, and CrossFit total. The lack of observed group differences is similar to the findings of De Oliveira et al [13] on maximal strength in young resistancetrained men undergoing HRV-guided training. However, De Oliveria et al [13] used HRV to augment training frequency, while we used HRV to modulate training intensity.…”
Section: Discussionsupporting
confidence: 90%
“…Endurance training programs utilizing HRV-guided individualization improve VO2peak, peak power in runners [11], and 40 min time trial performance in cyclists [10]. Additionally, resistance training frequency can be increased when using HRV to determine recovery intervals [13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Chen et al who reported that HRV, as a surrogate of autonomic nervous function, may accurately mirror recovery status following strength loadings in weightlifters [29], we can currently not support the use of HRV to accurately quantify recovery demands following distinct strength-loading patterns. Such a conclusion is in line with other recent findings showing no advantage in strength gains and muscle hypertrophy when strength training was performed with a predetermined protocol or program based on HRV recovery [30]. However, caution should be paid when interpreting our present findings as the low sample size somewhat limits the generalizability of our findings.…”
Section: Discussionsupporting
confidence: 90%
“…HRV is attractive to coaches because it is a non-invasive physiological marker that can be obtained in only a few minutes with inexpensive mobile applications [14]. HRV-guided RT may reduce the risk of overuse injuries [15] while producing comparable RT adaptations to standardized training in a shorter time-period (5 vs. 7 weeks) [16]. Though HRV and neuromuscular responses follow a similar time course for recovery from a single bout of RT at the group level, correlation analyses have not been performed [6,13].…”
Section: Introductionmentioning
confidence: 99%